Ecological reparation repair, remediation and resurgence in social and environmental conflict - Papadopoulos, Dimitris 1967-; Puig de la Bellacasa, María 1972-; Tacchetti, Maddalena (Dis-positions: troubling methods and theory in STS, 2023)
"How do we address the threat of social and environmental destruction while creating and maintaining liveable worlds? Expert scholars from diverse backgrounds unpack the question in this research-oriented, real-world challenges-focused collection. The authors explore practices of repairing damaged ecologies across different locations and geographies and propose innovative ideas for the conservation, mending, care and empowerment of human and non-human ecologies. This ground-breaking collection establishes ecological reparation as an urgent and essential topic of public and scholarly debate."